Deformation under a Young Volcanic Covered Area in Southern Garut, Indonesia: Insight from 3D Gravity Modelling - Ilham Arisbaya; Edy Wijanarko; Prihadi Sumintadireja; Warsa Warsa; Hendra Grandis (Directorate for Research and Community Services (LPPM) ITB, 2024)
Destructive earthquakes are frequently related to inland active faults. In recent years, a significant number of shallow earthquakes with low magnitude have occurred in southern Garut, West Java, Indonesia. Two earthquakes, with magnitudes of M4.2 and M3.9 in 2016 and 2017, respectively, have caused significant damage and were interpreted as indications of an active fault. We used publicly available gravity data to infer the subsurface structure that may be related to recent seismic activity. We used spectral analysis and filtering techniques for the regional-residual anomaly separation and anomaly enhancement to show the basin structure in the study area. 3D gravity inversion modelling was performed to obtain the subsurface density distribution. The result indicates the sedimentary layers with a density of 2.4 to 2.5 gr/cm3 with an underlying basement with a density of 2.65 gr/cm3. An intra-basin basement high with an NE-SW trend divides the basin into two sub-basins. This local basement high can be associated with a magmatic intrusion body and a series of young volcanic bodies located at the northeastern end of the basin. Our results emphasize a possible strong interaction between the tectonic and magmatic activities in this region.